Analisis Kemampuan Berpikir Kritis dalam Menyelesaikan Soal Berbasis Higher Order Thinking Skills (HOTS) pada Materi Aritmatika Sosial Peserta Didik Kelas VII - Febi Pratama; Anwas Mashuri; Budi Sasomo (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The criterion for students who have been able to think critically is when they can think systematically, besides having awareness in thinking, then they can see the difference between mistakes and truths. The purpose of this research is to measure the extent of students' ability to think critically on the completion of Higher Order Thinking Skill (HOTS) questions, especially in the subject of mathematics and social arithmetic material for grade VII students. This research is classified as qualitative descriptive research. The subjects involved were 6 students in grade VII D SMPN 3 Ngawi. The method used is qualitative descriptive with data analysis techniques using models from Miles & Huberman. Meanwhile, at the time of data collection, the instrument was in the form of 2 HOTS questions that were in accordance with the research subject. In data collection using tests and interviews, tests are used to measure cognitive competence while interviews are used as a follow-up to explore in depth related to students' answers. Based on a series of research processes, it can be proven that the students studied are divided into 3 categories of ability, namely low, medium, and high.